TEACHER´S QUALITY AND EXPERIENCE IN HIGH EDUCATION - Lafuente Guantes, María Isabel (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2011)
In this work it is considered the way of understanding the quality in the educational experience in the university from the practice of its professionals, and in relation with the educational current guidelines. There is analyzed in three works: the main ideas in  this experience is based, the value on the educational process, what conditions are needed to achieve quality and what its accomplishment demands.